Electromyographic activity of lower limbs to stop baseball batting - Hiroki, N.; Akito, M.; Michiko, Y.; Kazutoshi, K. (The Journal of Strength and Conditioning Research, 2012)
We investigated the muscle activation pattern of the lower limbs for the stopping motion of baseball batting by recording surface electromyography (EMG) from 8 muscles, the left and right rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), and medial gastrocnemius (MG) muscles. First, muscle activities for `Swing` and `Stopping` trials were examined in 10 skilled baseball players and 10 unskilled novices. Second, the characteristics of EMG activities for `Stopping` were compared between the 2 groups. The peak latencies of EMG were significantly shorter in `Stopping` than in `Swing` at the right-TA, left-BF, and left-MG between both groups. The peak amplitudes of EMG activity were significantly larger in `Swing` than in `Stopping` at the right-TA, left-BF, and left-MG in both groups. In addition, the peak amplitudes of EMG activity for `Stopping` were significantly larger in the players than in novices at the right-RF and right-TA. The characteristics of EMG activity clearly differed between `Swing` and `Stopping,` and between baseball players and nonplayers, indicating that evaluating the EMG activity in batting enables the understanding of proficiency. Our findings should help players, novices, and coaches to optimize batting performance.